Unique neoantigens arise from somatic mutations in patients with gastrointestinal cancers - Parkhurst, Maria R. (Cancer Discov, 2019)
Immunotherapies can mediate regression of human tumors with high mutation rates, but responses are rarely observed in patients with common epithelial cancers. This raises the question of whether patients with these common cancers harbor T lymphocytes that recognize mutant proteins expressed by autologous tumors which may represent ideal targets for immunotherapy. Using high throughput immunologic screening of mutant gene products identified via whole exome sequencing, we identified neoantigen reactive tumor infiltrating lymphocytes (TIL) from 62 of 75 (83%) patients with common gastrointestinal cancers. In total, 124 neoantigen reactive TIL populations were identified, and all but one of the neoantigenic determinants were unique. The results of in vitro T cell recognition assays demonstrated that 1.6% of the gene products encoded by somatic non-synonymous mutations were immunogenic. These findings demonstrate that the majority of common epithelial cancers elicit immune recognition and open possibilities for cell based immunotherapies for patients bearing these cancers.